STOICHIOMETRIC ANALYSIS SYSTEM FOR PRODUCTION OF SOAP FROM VEGETABLE OIL RESIDUAL: A STRATEGY FOR REDUCING ENVIRONMENTAL IMPACT - Thode Filho, Sérgio; Sena, Marcelo Fonseca Monteiro de; Silva, Elmo Rodrigues da; Cabral, Gabrielle Borges; Maranhão, Fabíola da Silveira (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2013)
The manufacture of soap using waste vegetable oil is one of the ways to avoid it reaches water bodies and soil in its ruling, thus mitigating their impacts on the environment. His artisanal does not require much investment and knowledge, it is a simple process that uses inputs and equipment used in the daily lives of most people. This work aims at presenting the results of an analysis system that would provide a good reason between the inputs used in the production of soap from vegetable oil waste. Based on these results, it was made possible the production of a soap with acceptable physical and chemical characteristics, of satisfactory quality similar to industrialized and, indirectly, the awareness of the inappropriate disposal of vegetable oil.